From Local Community to Modern Conurbation: The Development of Lekki Peninsula of Lagos, 1950 – 1981 - Sanni, Habeeb Abiodun; Boge, Faruq Idowu (South Asian Journal of Social Sciences and Humanities, 2021)
It is incontestable that the modern Lekki Peninsula morphed from a purely agrarian, rural and traditional society. In contemporary Lagos State (the commercial nerve of Nigeria), communities within the Lekki Peninsula remain a combination of rapidly growing built-up urban areas. As a part of a transformation process, there is a large form of residential, commercial, and industrial activities currently going on within the area. Acquisition of lands and accommodation within the area has become one of the most expensive in Lagos State. On the basis of the foregoing assertions, this paper examines the historical origin of the developments that have been witnessed in modern Lekki Peninsula. It specifically traces the factors that promoted the transformation of the Peninsula from a traditional society to an urban centre. It further examines the consequences of these transformations on the indigenous people and the pre-existing traditional communities. Using the historical approach to data collation and interpretations, the study adopts the qualitative research methodology. The paper argues that the Lekki Peninsula has overtime enjoyed a rapid spate of transformation, urbanisation and development, which were promoted by such factors as colonial experience, proximity to the city of Lagos, and some deliberate policies of the government among others.